PROBLEMATIKA ISBAT NIKAH POLIGAMI SIRRI - Mukhtaruddin Bahrum (Al-Adalah: Jurnal Hukum dan Politik Islam, 2019)
The law No. 1 of 1974 concerning marriages annunciates that the success of marriages conducted must be by their religion and beliefs, in addition to being valid and approved by the state, therefore marriages must be approved by those invited. However, in reality, some people deviate from marriage registration requirements. The cause is not only lack of people's awareness to register a marriage, also driven by the difficulty to obtain permission to do polygamy, thus those who want to do polygamy prefer sirri polygamy. The awareness of how important the marriage registration is will only arise if in the future there is an interest in dealing with the law. These things encourage someone to ask for marriage isbat upon the sirri polygamy in the Religious Court. Therefore, marriage isbat upon Sirri polygamy will cause positive and negative effects in its implementation. To discuss the positive and negative effects of sirri polygamy marriage, the researcher uses normative juridical research methods with qualitative descriptive research analysis. The results showed that from a positive perspective, marriage is required for Sirri marriage to get a Legal Guarantee (Article 6 Paragraph 2 KHI). Since with the stipulation of Sirri polygamy, candidates of Sirri polygamy have a basis to get a marriage book (Article 7 Paragraph 1 KHI). As a result, there is an increase regarding the social status in the community that was once Sirri has now become official. Besides, the changes occur in the status of children as well as rights in shared assets and inheritance before the law. While from the negative side, if the Sirri polygamy is granted and/or the marriage is accepted, it means those who has deviated the law are approved and justified. The indirect impact is the assertion of values that must be issued by the provisions regarding the requirements of polygamy. Therefore, based on SEMA No. 3 of 2018, the Supreme Court no longer gives the permission to ratify Sirri polygamy.